New Brunswick at the Crossroads : Literary Ferment and Social Change in the East - Tremblay, M. Anthony (Michael Anthony), 1962- (Book collections on Project MUSE., 2017)
What is the relationship between literature and the society in which it incubates? Are there common political, social, and economic factors that predominate during periods of heightened literary activity? New Brunswick at the Crossroads: Literary Ferment and Social Change in the East considers these questions and explores the relationships between periods of creative ferment in New Brunswick and the socio-cultural conditions of those times. The province's literature is ideally suited to such a study because of its bicultural character--in both English and French, periods of intense literary creativity occurred at different times and for different reasons. What emerges is a cultural geography in New Brunswick that has existed not in isolation from the rest of Canada but often at the creative forefront of imagined alternatives in identity and citizenship. At a time when cultural industries are threatened by forces that seek to negate difference and impose uniformity, New Brunswick at the Crossroads provides an understanding of the intersection of cultures and social economies, contributing to critical discussions about what constitutes "the creative" in Canadian society, especially in rural, non-central spaces like New Brunswick.